2015
DOI: 10.18632/oncotarget.3118
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin-1, induced by Aurora-A but inhibited by BRCA2, promotes ovarian cancer metastasis

Abstract: While Aurora-A (Aur A) provokes, BRCA2 restrains primary tumorigenesis, the roles of Aur A and BRCA2 in cancer metastasis remains unclear. Here, we show that the metastatic promoting markers SLUG, FBN1, and MMP2, 9, 13 are either stimulated or suppressed by Aur A or BRCA2, but the metastatic suppressors E-cadherin, β-catenin, and p53 are either inhibited or promoted by Aur A or BRCA2, leading to enhanced or reduced cell migration and invasion. Further study suggests that FBN1 inhibits E-cadherin and β-catenin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 50 publications
3
55
0
4
Order By: Relevance
“…Lentivirus carrying SIRT3 shRNA or STAT3 was generated and harvested as described previously. 34 Briefly, the cells were infected twice for a total of 4 days (2 days for each infection), and the positive clones were selected with puro23in (200 ng/mL) for 7-10 days. Control cell lines were generated by infection with viruses containing the empty vector following the same protocol.…”
Section: Plasmid Construction and Cell Transfectionmentioning
confidence: 99%
“…Lentivirus carrying SIRT3 shRNA or STAT3 was generated and harvested as described previously. 34 Briefly, the cells were infected twice for a total of 4 days (2 days for each infection), and the positive clones were selected with puro23in (200 ng/mL) for 7-10 days. Control cell lines were generated by infection with viruses containing the empty vector following the same protocol.…”
Section: Plasmid Construction and Cell Transfectionmentioning
confidence: 99%
“…Similarly, the depletion of lncRNA prostate cancer-associated transcript 1 has led to the repressed cell invasion, migration, proliferation, and EMT of osteosarcoma cells [35]. Also, ovarian cancer migration and invasion were revealed to be attenuated following FBN1 silencing [36]. Consistently, elevating the expression of miR-140…”
Section: Discussionmentioning
confidence: 91%
“…41 As for ovarian cancers, BRCA2 inhibited ovarian cancer cell metastasis by regulating metastatic promoting markers (SLUG, FBN1, and MMP2, -9, -13), and overexpression of BRCA2 correlated with favorable DFS and OS in ovarian cancer patients. 42 Another study also showed that BRCA2 expression is associated with early-stage disease, low ascites incidence, younger age at diagnosis and low-grade tumors in endometrioid ovarian carcinoma patients. 43 This indicates the tumor suppressor role of BRCA2 in several cancers including ovarian cancer.…”
Section: Rp11-552m114 and Brca2 In Regulating A-2780 Cellsmentioning
confidence: 95%